Предмет: Математика,
автор: zabrodina1979
(0,2х-3)-(х-2)
(-4а+3,1х)-(1,7а-3,5х)
(-1,99а+2,5)-(5,6а-9,7)
(-5,6у-3)+(6,4у-9,9)
Здравствуйте!Помогите пожалуйста с решением
Ответы
Автор ответа:
0
(0,2х-3)-(х-2)=0,2x-3-x+2=-0,8x-1
(-4а+3,1х)-(1,7а-3,5х)= -4a+3,1x-1,7a+3,5x= -5,7a+6,6x
(-1,99а+2,5)-(5,6а-9,7)= -1,99a+2,5-5,6a+9,7= -7,59a+12,2
(-5,6у-3)+(6,4у-9,9)= -5,6y-3+6,4y-9,9=0,8y-12,9
(-4а+3,1х)-(1,7а-3,5х)= -4a+3,1x-1,7a+3,5x= -5,7a+6,6x
(-1,99а+2,5)-(5,6а-9,7)= -1,99a+2,5-5,6a+9,7= -7,59a+12,2
(-5,6у-3)+(6,4у-9,9)= -5,6y-3+6,4y-9,9=0,8y-12,9
Похожие вопросы
Предмет: География,
автор: nazschurko
Предмет: География,
автор: zhensyxx
Предмет: География,
автор: krylu0509kivska
Предмет: Математика,
автор: Zelenkova1anastasia